The Use Of Tiktok Social Media On The @Nyaimercon Brand To Form Positioning - Aldy Pratisara Wirya; Itca Istia Wahyuni (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
Globalization has led the world community to the era of the industrial revolution 4.0, this has also triggered the increasing use of social media and online media by all components of society in carrying out their daily lives. One of them is the content produced by the TikTok application. Currently, TikTok is one of the most popular applications in the world. One industry that sees the opportunity of TikTok media is instant culinary @Nyaimercon to carry out its marketing strategy through TikTok online media to form positioning. In this study, TikTok social media is analyzed by looking at Tiktok @Nyaimeron social media as a marketing strategy with a total of 59.7 thousand followers through aspects of message frequency, message feedback, attractiveness and clarity of the messages conveyed. For positioning, the data analysis used is based on the results of researcher interviews with sources selected from internal parties, namely sources from Marshwillow cosmetics marketing communication, TikTok Content Creator and Social Media specialist. The results showed that Tiktok social media both directly and indirectly has a significant role in shaping @nyaimercon's product positioning. Suggestions related to Nyai Mercon's brand positioning after seeing and observing TikTok as a social media marketing strategy include creating content ideas for eating or processing Nyaimercon products that are more interesting and have never existed before.